The total synthesis of (-)-paraherquamide A - Cao, Jianhua, author; Williams, Robert M., advisor (Colorado State University. Libraries, 2000)
The first stereocontrolled total synthesis of (-)-paraherquamide A is described in 48 chemical steps. The synthesis is a convergent one, starting from ethyl glycinate, ethyl acrylate and vanillin. The longest linear route is 35 steps. Vanillin was acetylated and nitrated to provide nitrovanillins (94 and 95). These were converted to the azalactones, hydrolyzed to the α-ketocarboxylic acids, oxidatively decarboxylated to acids 99 and 108. Compound 99 was reductively cyclized to oxindoles 100, which was then demethylated to give pure oxindole 101. The oxindole was regioselectively prenylated, epoxidized, and subjected to a key seven-membered ring forming procedure to provide the unique dioxepin 104. Compound 104 was reduced to indole 105 and indoline 106 which was converted to 105 by reaction with DDQ. Indole 105 was protected and subjected to a Mannich reaction to afford the gramine derivative 60. The Michael adduct 150 from ethyl glycinate and ethyl acrylate was protected, intramolecularly condensed and reduced with Baker's yeast to give cis-β-hydroxy proline ester 129. Stereoselective α-alkylation of 129, protection, deprotection, bromoacetyl amide formation, aminolysis, cyclization and dimethoxycarbonylation provided diketopiperazine (DKP) 91. DKP 91 was alkylated with compound 60 to provide indoles 303 and 304, which were then individually decarbomethoxylated to afford four separable diastereomers anti-305 (305E/Z) and syn-306 (306E/Z). These four diastereomers were individually converted to the corresponding SN2' substrates through lactim ether formation, protection of the indole nitrogen, deprotection, allylic chloride formation and TBS ether formation. SN2' cyclization of these four SN2' substrates individually provided the same product 327. Cyclization of lactim ether 327, ring opening of the lactim ether moiety and ring closure afforded DKP 338. Selective amide group reduction of 338, N-methylation, MOM ether deprotection, oxidation, bis-deprotection by TFA provided indole-ketone 344. Oxidative spirooxidation of 344 followed by dehydration gave ketone-olefin 43. Stereoselective methyl addition to 43 afforded (-)-paraherquamide A.
Keywords: Antibiotics -- Synthesis